Developing of a library operations manual for the Matayuncab Elementary School Library - Carpio, Jenivie Roman (School of Library and Information Studies, University of the Philippines Diliman, 2019)
The Matayuncab Elementary School (MES) Library is approximately 40 sq. m. and is considered an inactive room. It has a limited collection of books; with as of December 2018, the number of books the library approximates to a 100 volumes, at most. There is a need to find donors for additional collections. In the absence of an operations manual, the researcher finds the MES Library Manual to be in need of help in assisting the personnel to operate the library properly.